Development of thin layer chromatography bioautographic determinaton of a-glucosidase inhibition activity of lagerstroemia speciosa - Abe, Charissa Amiera
Lagerstroemia speciosa (L.) Pers. (Lythraceae), known as banaba, has been used as a folk medicine for the treatment of diabetes mellitus. One of the mechanisms to be accounted for its hypoglycemic effect is through inhibition of the a-glucosidase enzyme. The aim of this study is to develop a TLC bioautographic method of separation of components and localization of a-glucosidase inhibitory activity of banaba leaf extract. The following solvent systems were used in the optimization: hexane-ethyl acetate-acetic acid, hexane-ethyl acetate-methanol-acetic acid, chroroform-acetone, DCM-methanol and ethyl acetate-methanol; and the following assay conditions were modified for the optimization of TLC a-glucosidase inhibition assay: order and manner of application of reaction solutions to TLC plate, incubation time and sample and reaction solution concentrations. The best chromatograms were produced using the following solvents: hexane-ethyl acetate acid for crude ethanolic extract, hexane fraction and DCM fraction; hexane-ethyl acetate-methanol-acetic acid for ethyl acetate fraction; and ethyl acetate-methanol for the water fraction; and optimum assay conditions were found to be the following: manual dipping of the plates, face-down, to the reaction solutions in the following order: substrate, enzyme, and chromogenic agent; incubation period of 15 min at 30-35oC, and concentrations 2 U/mL a-glucosidase, 1 mg/mL 2-naphthyl-a-Dglucopyranoside, 1.5 mg/mL FBS, and 1 mg/mL sampl solutions. The crude extract produced zones of inhibition found at the point of application and at Rf 0.11; the water fraction at the point of application, and the ethyl acetate fraction at the point of application and at Rf 0.33. The assay has proved to be beneficial in detecting antidiabetic property of compounds in complex matrices such as plant extracts, thus, may be useful in the earlier part of drug discovery for compounds with antidiabetic property.